Mixed germ cell tumour complicated by pulmonary thromboembolism: a case report - Kukreja, Hema Priya; Talwar, Prathap; Bhandiwad, Ambarish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Malignant ovarian germ cell tumours (MOGCTs) are a heterogeneous group of tumours that have several histological different types derived from primordial germ cells of the embryonic gonad. They account for less than 5% of all ovarian malignancies, and are seen in the second and third decade of life. The majority of germ cell tumours are diagnosed in the early stages. Histology, FIGO stage and residual tumour after surgery are the most important prognostic factors. Recent multimodality therapy with staging laparotomy and conservative surgery, followed by platinum based chemotherapy, is associated with survival rates of 60 - 80%, even in patients with advanced disease. Mixed germ cell tumours are extremely rare and the prognosis depends on the size of each component of the tumour. The exact incidence of thrombo embolic events in patients with malignancy is difficult to determine. However ovarian malignancy is strongly associated with venous thrombo embolism. We report a case of a fourteen year old girl with a mixed GCT, with elements of yolk sac tumour and embryonal carcinoma, who succumbed to pulmonary thromboembolism.